Upgradation of 82.6GHz ECRH system for SST-1 and Aditya-U - Shukla Braj Kishore; Patel Jatin; Patel Harshida; Mistry Hardik; Purohit Dharmesh; Parmar K.G.; Tai Evgeny; Soluyanova E.; Khailov I.P.; Bakulin M.I. (EPJ Web of Conferences)
In SST-1 and Aditya-U Tokamaks, two ECRH systems (42GHz-500kW and 82.6GHz-200k) are used to carry out various experiments related to ECRH assisted plasma start-up and heating at fundamental and second harmonic. The SST-1 tokamak is operated at 1.5T magnetic field and 42GHz ECRH system has been extensively for plasma start-up and heating. The 82.6GHz ECRH could not be used thoroughly due limitation in power as 200kW power is not enough for breakdown in SST-1 at second harmonic. The original 82.6GHz-200kW ECRH system is being upgraded in terms of ECRH power to carry out experiment at higher power. The 82.6GHz-200kW Gyrotron has been upgraded to 400kW power. The Gyrotron has been tested successfully at factory and delivers 400kW power at 48kV cathode voltage and draw around 20A cathode current, the efficiency of Gyrotron is around 42%. The 82.6GHz Gyrotron will be commissioned at IPR and the total ECRH power 0.9MW (0.5MW at 42GHz and 0.4MW at 82.6GHz) will facilitate to carry out ECR heating experiments simultaneously at fundamental and second harmonic. The paper presents the recent test results of 82.6GHz-400kW Gyrotron and discusses the experimental plan with upgraded ECRH system.